Persepsi Siswa Terhadap Penggunaan Aplikasi TikTok Dalam Pembelajaran Bahasa Jepang - Nova Zira Fitria; Damai Yani (Universitas Negeri Padang, 2023)
This research is motivated by the phenomenon of using the TikTok application among students or students including in learning with the aim of seeing the relevance of using the TikTok application in Japanese language learning and students' views or assessments of the use of TikTok application-based media as learning media. This research uses a qualitative approach with a descriptive case study design with the number of research respondents as many as 24 students of class XI IPA 1 SMA PGRI 1 Padang. Data collection was carried out by distributing questionnaires and semi-structured interviews. The data in this study were obtained based on statements from the results of distributing questionnaires and in-depth interviews with respondents. The instrument used to collect data consisted of 20 statements in a questionnaire and semi-structured interview questions. Based on the results of the questionnaire analysis, it is known that the student's perception or response to the use of the TikTok application in learning Japanese obtained a range of positive perception categories with an average of 81.93%. Then based on the interview analysis results dominated by the positive perceptions that the application's use in the learning of Japanese can arouse student learning interest, so it can be concluded that the app has a positive value in Japanese learning.